A Polyurethane Based Composite with Mechanically Enhanced Performance for Bone repair. (2019) - Zhang, Yuanchi; Hu, Jinlian
Abstract: As one of the most important organs in body, bones always play a key role for supporting body and protecting the soft tissues. However, with the population aging, bone defect becomes a common situation owing to bone fracture, osteoporosis, diseases and so on. Traditional treatments including bone grafts and conventional metal implantations have apparent drawbacks during the procedure of bone repairing such as time-consuming, labor-intensive and inflammation-responsive, thus artificial materials especially the polymer materials have gained increased attractions. Nowadays, these materials have been applied for bone repair even in the clinical trials. Shape memory polymers (SMPs) as one of the smart artificial materials have attracted increasing attentions due to their unique features. SMPs can achieve the function memorizing deformed shapes and then recover upon expose to an external stimulus, which is different from other biomedical materials. What is more, their shapes and sizes even the properties can be designed to meet various demands. In this study, a poly (ε-caprolactone) based shape memory polyurethane was modified with hydroxyapatite (HA) to fabricate the SMP/HA composites. Then, the structure, mechanical properties and shape memory behaviors were characterized. The results suggested that adding 2 wt% HA could achieve the best mechanical and memory properties in the composites for bone repair. We have full confidence that this composite has huge potential in the biomedical area particularly for bone repair.